MODERN METHODOLOGY OF TEACHING EXISTING LANGUAGES IN THE PROCESS OF PRESCHOOL EDUCATION - IN CHINA (Intent Research Scientific Journal, 2023)
There was a talk about teaching, teaching, and modern methods of languages in three preschool educational processes. From this, the methods and examples of this methodology are loaded using the Hoti